Improving rate of gelatin/carboxymethylcellulose dissolving microneedle for transdermal drug delivery - Nur Afiqah Mustafa Kamal,; Ishak Ahmad,; Suria Ramli,; Tuan Mazlelaa Tuan Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Gelatin has been widely used as a nature-derived biopolymer material due to its high biocompatibility and abundance. However, multiple fabrication steps for the moulding process may limit its application to microneedle technology as biomedical application. This research focused on physical, chemical, and mechanical characteristics of gelatin-based dissolving microneedle (DMN) by adding in various concentrations of carboxymethylcellulose. Carboxymethylcellulose (CMC) derived from kenaf bast fibre were extracted by alkaline treatment and esterification process, followed by fabrication of DMN with gelatin using centrifuge-casting method. The formulation of G/CMC6 demonstrated the highest mechanical strength of 11.2 N by texture analyzer; hence, G/CMC6 was chosen for further investigate of its intra- and intermolecular bond, amorphous study, and its geometry by Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). FTIR showed various chemical interactions involved including hydrogen bonding, dipole-dipole and charge effect. The XRD result shows amorphous peak of gelatin decreased at 2θ = 20 - 21° with the addition of CMC. The height of microneedle arrays also decreased from its micromould by 36.7% due to agglomeration of CMC. Considering the biodegradability and the improvement of gelatinbased DMN mechanical properties by carboxymethylcellulose, the combination of gelatin and CMC is one of great potential for delivering drugs using microneedle.